PAPUQ PARENTING STYLES ON CHILDREN'S LANGUAGE DEVELOPMENT AGED 5-6 YEARS (CASE STUDY AT KARANG SIDEMEN VILLAGE NORTH BATUKLIANG) - Suhaena Maolani (JOETAL: Journal of Education, Teaching and Learning, 2025)
This study aims to determine the "papuq" parenting style on language development and to determine its impact on the language development of children aged 5-6 years, known as the "golden age." The research approach used in this study is qualitative descriptive. The data sources were "papuq" who were caring for their grandchildren from broken homes aged 5-6 years. Data collection techniques in this study included observation, interviews, and documentation. Data analysis in this study included data collection, data reduction, and drawing conclusions. Data validity was checked using triangulation techniques by comparing observational data with interview results and interview results with documentation. Based on the results of this study, (1) the "papuq" bedengah method in developing children's language development varies, including authoritarian bedengah, permissive bedengah, and democratic bedengah. "papuq" who applies authoritarian bedengah tends to be strict, forcing children and scolding children in a high tone of voice even to the point of hitting children to become fearful and insecure, permissive bedengah tends to spoil children so that children become willful, rebellious and less independent While democratic bedengah applies warm parenting, giving children the freedom to express their opinions children become obedient and confident. (2) The impact of the "Papuq" parenting style on children's language development is that children are able to understand language, but some children are not yet able to express it. They are quieter, do not understand commands simultaneously, and when asked questions, their answers do not match the question. They also tend to use a high-pitched voice when angry. Children communicate using the Sasak language with the words ape "what" and aoq "yes." They interact using child-like language such as maum "eat," wowok "feed," and bobok "sleep." They are not yet familiar with all the concepts of the letters of the alphabet A-Z.